Unveiling the impacts of eWOM on tourist revisit intention from a cognitive perspective: the moderating role of trade-offs - Thong Van Pham; Tam Duc Le; Kim Thoa Dang Thi; Thuy Linh Nguyen; Thi Nguyen Thao Tran (Cogent Business & Management)
Despite the efforts of the government and managers to promote tourism in the context of the economic downturn, tourism recovery has been slow. Tourist revisit intention is a significant factor in considering tourist loyalty to a destination. This research seeks to investigate the mechanism of tourist revisit intention via the impact of eWOM as a substitute for tourism advertisements that have become too familiar and obscure. The cross-sectional research was carried out by convenience sampling with the involvement of 351 visitors in central Vietnam. The study evaluated the measurement model to ensure the suitability of the scales as well as assessed the structural model and tested the proposed hypotheses using SmartPls software. The research results indicated that eWOM significantly impacts tourist engagement (TE) and perceived value (PV), shedding light on tourist motivation (MT), satisfaction (SA), and revisit intention (RE). Notably, trade-offs (TR) related to monetary and non-monetary costs negatively moderate the association between PV and RE. The highlights of this study are the mediating influence of cognitive processes and the moderating influence of trade-offs, shaping RE in the current context.